INISIASI MENYUSU DINI MENJAMIN KECUKUPAN ASUPAN ASI - Nursanti, Ida (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: Breastfeeding is the best way of providing ideal food for babies? growth. Exclusive breastfeeding appropriate to the needs of babies is recommended considering the benefits of breastfeeding for the next phase of life. Optimal breastfeeding management will affect the adequacy of breast milk intake in babies. Volume of milk produced by lactating mothers is closely related to the earlytime of breastfeeding. One factor likely to lead to inadequate intake of milk is unimplemented practice of early initiation of breastfeeding at the first hour after birth. Objective: To determine the implementation of early initiation of breastfeeding (EIB), to determine the adequate in take of milk to the newborn, to determine the relationship of EIB implementation to adequate in take of milk and to determine the effect of IEB implementation on the adequacy of breast milk intake in new borns. Methods: This was an observational study with a prospective cohort design using quantitative approach. The number of samples was 92 pairs of mother-baby determined by purposive sampling. Data were collected by observation using monitoring sheets. Statistical tests used were Chi-square (x²) at the significance level of p <0.05, to see the magnitude of the risk of the effect (outcome) seen in the RR with the confidence interval (CI) 95%. Results: The majority of babies was initiated early breastfeeding and received a good adequacy of breastmilk. There was a significant association between early initiation of breastfeeding (EIB) and adequate in take of breastmilk (p = 0.001) and EIB in creased the chances to the baby to get adequate intake of milk (RR = 2.0). Conclusion: Babies who received early initiation of breastfeeding had a better chance to get adequate intake of milk than those who did not receive early initiation of breastfeeding. Keyword: Healthily born baby, early initiation of breastfeeding, adequate intake of breast milk